Phenotypic and genetic characteristics of 130 patients with mucopolysaccharidosis type II: A single-center retrospective study in China - Zhang, Zhenjie; Ma, Mingsheng; Zhang, Weimin; Zhou, Yu; Yao, Fengxia; Zhu, Lisi; Wei, Min; Qiu, Zhengqing (Frontiers in Genetics, 2023)
Background: Mucopolysaccharidosis Type II (MPS II) is a rare, progressive and ultimately fatal X-linked lysosomal storage disorder caused by mutations in the iduronate-2-sulfatase (IDS) gene. This report conducted a retrospective analysis to investigate the clinical characteristics, genotypes and management strategies in a large cohort of Chinese patients with MPS II. Methods: In this study, we explored 130 Chinese patients with MPS II between September 2008 and April 2022. Clinical manifestations, auxiliary examination, IDS pathogenic gene variants and IDS enzyme activity, surgical history were analysed in the study. Results: A total of 130 patients were enrolled and the mean age at diagnosis was 5 years old. This study found the most common symptoms in our patients were claw-like hands, followed by coarse facial features, birthmarks (Mongolian spot), delayed development, inguinal or umbilical hernia. The most commonly cardiac manifestations were valve abnormalities, which were mitral/ tricuspid valve regurgitation (71.9%) and aortic/ pulmonary valve regurgitation (36.8%). We had found 43 different IDS pathogenic gene variants in 55 patients, included 16 novel variants. The variants were concentrated in exon 9 (20%=11/55), exon 3 (20%=11/55) and exon 8 (15%=8/55). A total of 50 patients (38.5%) underwent surgical treatment, receiving a total of 63 surgeries. The average age of first surgery was 2.6 years, and the majority of surgery (85.7%, 54/63) was operated before 4 years old. The most common and earliest surgery was hernia repair. Three patients were died of respiratory failure. Conclusions: This study provided additional information on the clinical, cardiac ultrasound and surgical procedure in MPS II patients. Our study expanded the genotype spectrum of MPS II. Based on these data, characterization of MPS II patients group could be used to early diagnosis and treatment of the disease.